Digital platforms and profitability of farmers in the Mantaro valley, Huancayo - Arteaga Untiveros, Luis Enrique (2023)
Objective: To determine the relationship between digital platforms and the profitability of farmers in the Mantaro valley in Huancayo. Methods: A quantitative approach was employed using a non-experimental cross-sectional design of applied research. A total of 363 farmers from the districts of El Tambo, Huancayo, Chilca, Sapallanga and Huancán were surveyed, representing areas with a high concentration of agriculture and internet access. The Spearmen test was used to assess correlations. Results: A moderately positive association (Rho = 0,563) between the variables is revealed. Social networks, such as Facebook and YouTube, and messaging apps such as WhatsApp and Facebook Messenger, show moderately positive correlations, while other digital platforms such as video conferencing, emails and Google forms have a positively low correlation. Virtual stores and specialized applications are not used in commercial activities. Conclusion: Digital platforms maintain a moderately positive relationship with agricultural profitability, influenced by limited access, language barriers, preference for traditional methods, and data security concerns.